2019
DOI: 10.1002/tox.22827
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gestational low protein diet and postnatal bisphenol A exposure on chemically induced mammary carcinogenesis in female offspring rats

Abstract: This study evaluated the effect of gestational low protein diet (LPD) and/or postnatal bisphenol A (BPA) exposure on mammary gland development and carcinogenesis in female offspring. Pregnant Sprague‐Dawley rats were fed a normal protein diet (NPD, 17% protein) or LPD (6% protein). At weaning, female offspring were distributed in four groups (NPD, LPD, NPD + BPA, and LPD + BPA) and received vehicle or BPA in drinking water (0.1%), during postnatal day (PND) 21 to 51. On PND 51, some female offspring were eutha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…Body weight at birth (PND 1) and weaning (PND 21) and body weight evolution of groups are indicated in Table 1 . In the present study, we observed that maternal low protein restriction influenced offspring body weight, which is in line with other experimental and human studies ( Fernandez-Twinn et al, 2007 ; Herring et al, 2018 ; Bautista et al, 2019 ; Varuzza et al, 2019 ; Yang et al, 2020 ). During the experimental period (PND 1 to PND 250), the body weight of female offspring whose dams were fed an LPD was significantly lower ( p < 0.001) than female offspring whose dams were fed with NPD.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Body weight at birth (PND 1) and weaning (PND 21) and body weight evolution of groups are indicated in Table 1 . In the present study, we observed that maternal low protein restriction influenced offspring body weight, which is in line with other experimental and human studies ( Fernandez-Twinn et al, 2007 ; Herring et al, 2018 ; Bautista et al, 2019 ; Varuzza et al, 2019 ; Yang et al, 2020 ). During the experimental period (PND 1 to PND 250), the body weight of female offspring whose dams were fed an LPD was significantly lower ( p < 0.001) than female offspring whose dams were fed with NPD.…”
Section: Resultssupporting
confidence: 93%
“…Besides, the chemically induced carcinogenesis model is an important tool to study the multistep process of mammary carcinogenesis (Russo and Russo, 1996;Russo, 2015). Using a maternal LPD model, our research group and others reported important changes in several organs, such as liver, mammary gland, pancreas, prostate, and adipose tissue (Plank et al, 2006;Fernandez-Twinn et al, 2007;Beinder et al, 2014;Santos et al, 2019;Varuzza et al, 2019;Alejandro et al, 2020;de Oliveira Lira et al, 2020). Fernandez-Twinn et al (2007) were the first to demonstrate the adverse effects of gestational and lactational LPD on N-methyl-N-nitrosourea (MNU)-induced mammary carcinogenesis model in female offspring from Wistar rats, using a total of three 50 mg/kg body weight (b.w.)…”
Section: Introductionmentioning
confidence: 92%
“…Environmental concentration of BPA exposure can increase the risk of cancer 23 . Additionally, epidemiological and experimental studies suggest that BPA exposure early in life may have permanent and adverse effects on the health of developing organisms 24 . Broadly, this indicated that the effect of the low level of BPA exposure on infants should be pained more attention.…”
Section: Discussionmentioning
confidence: 99%
“…23 Additionally, epidemiological and experimental studies suggest that BPA exposure early in life may have permanent and adverse effects on the health of developing organisms. 24 Broadly, this indicated that the effect of the low level of BPA exposure on infants should be pained more attention. In this study, we conducted a manner of perinatal BPA exposure via drinking water.…”
Section: Effects Of Bpa Exposure On Splenic Ahr and Autophagy Signali...mentioning
confidence: 99%
“…Several studies pointed to an increased incidence of cardiometabolic disease, diabetes, and schizophrenia in individuals born during this period [ 7 , 8 , 9 ]. In addition, experimental and epidemiological studies also support the DOHAD concept and point out that exposure to adverse environmental conditions during early life impacts not only the incidence of non-communicable chronic diseases but also triggers the carcinogenesis process, including breast and prostate cancer, in descendants [ 10 , 11 , 12 , 13 , 14 , 15 ]. In this regard, Elias et al (2004) [ 16 ] found that girls (2 to 9 years old) exposed to famine during the Dutch hunger winter had a higher incidence of breast cancer.…”
Section: Introductionmentioning
confidence: 99%